Central bank digital currency: Stability and information - Cyril Monnet; Todd Keister (Swiss National Bank, Study Center Gerzensee, 2022)
We study how the introduction of a central bank digital currency (CBDC) would affect the stability of the banking system. We present a model that captures a concern commonly raised in policy discussions: the option to hold CBDC can increase the incentive for depositors to run on weak banks. Our model highlights two countervailing effects. First, banks do less maturity transformation when depositors have access to CBDC, which leaves them less exposed to depositor runs. Second, monitoring the flow of funds into CBDC allows policymakers to more quickly identify weak banks and take appropriate action, which also decreases the incentive for depositors to run. Our results suggest that a well-designed CBDC may decrease rather than increase financial fragility.
Keywords: E43; E58; G21; 330; CBDC; digital currency; financial stability; bank runs